2019
DOI: 10.1186/s40900-019-0161-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the acceptability of a co-produced and co-delivered mental health public engagement festival: Mental Health Matters, Jakarta, Indonesia

Abstract: Background Public engagement events are an important early strategy in developing a meaningful research agenda, which is more impactful and beneficial to the population. Evidence indicates the potential of such activities to promote mental health literacy. However, this has not yet been explored in Indonesia. Aim This paper describes a mental health public engagement festival carried out in Indonesia in November 2018 and uses evaluation data to consider the acceptabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…In contrast with European countries, patients and their families should be considered as one unit and attempts to reduce stigma and promote civic engagement should empower individuals at a community level. There is promising evidence on the use of community engagement events incorporating arts-based activities to reduce stigma through increased intergroup contact and enhanced knowledge about mental illness [59][60][61]. This study points to the need to ensure these social contact methods are locally contextualised for use in Indonesia.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast with European countries, patients and their families should be considered as one unit and attempts to reduce stigma and promote civic engagement should empower individuals at a community level. There is promising evidence on the use of community engagement events incorporating arts-based activities to reduce stigma through increased intergroup contact and enhanced knowledge about mental illness [59][60][61]. This study points to the need to ensure these social contact methods are locally contextualised for use in Indonesia.…”
Section: Discussionmentioning
confidence: 89%
“…Recent evidence suggests that one way to increase awareness of mental health and reduce stigma is through public engagement events which include education and art‐based activities and promote interpersonal contact between people with mental health problems and the public . A recent evaluation of a mental health festival in Indonesia further demonstrates the potential utility of such approaches within Indonesian contexts …”
Section: Discussionmentioning
confidence: 99%
“…One event took place in an air raid shelter [ 42 ] and three in a performing arts space [ 37 , 39 , 40 ]. Two of the eight festivals were on the topic of mental health [ 37 , 40 ]. One of the studies aimed to evaluate the whole festival [ 36 ], whilst the other seven studies evaluated a specific element of the festival.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies reported on the marketing of their public engagement event [ 36 , 37 ] with one study including social media analytics as part of their marketing assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation